Autophagy and Autophagy-Related Proteins in CNS Autoimmunity - Keller, Christian W.; Lünemann, Jan D. (Frontiers in Immunology, 2017)
Autophagy comprises a heterogeneous group of cellular pathways that enables eukaryotic cells to deliver cytoplasmic constituents for lysosomal degradation, to recycle nutrients and to survive during starvation. In addition to these primordial functions, autophagy has emerged as a key mechanism in orchestrating innate and adaptive immune responses and to shape CD4+ T cell immunity through delivery of peptides to MHC class II loading compartments. Individual autophagy proteins additionally modulate expression of MHC class I molecules for CD8+ T cell activation. The emergence and expansion of autoreactive CD4+ and CD8+ T cells are considered to play a key role in the pathogenesis of multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE). Expression of the essential autophagy-related protein 5 (Atg5), which supports T lymphocyte survival and proliferation, is increased in T cells isolated from blood or brain tissues from patients with relapsing-remitting MS. Whether Atgs contribute to the activation of autoreactive T cells through autophagy-mediated antigen presentation is incompletely understood. Here, we discuss the complex functions of autophagy proteins and pathways in regulating T cell immunity and its potential role in the development and progression of MS.